Inequalities in short-acting reversible, long-acting reversible and permanent contraception use among currently married women in India - Milan Das; Abhishek Anand; Babul Hossain; Salmaan Ansari (BMC, 2022)
Abstract Background In India, the usage of modern contraception methods among women is relatively lower in comparison to other developed economies. Even within India, there is a state-wise variation in family planning use that leads to unintended pregnancies. Significantly less evidence is available regarding the determinants of modern contraception use and the level of inequalities associated with this. Therefore, the present study has examined the level of inequalities in modern contraception use among currently married women in India. Methods This study used the fourth round of National Family Health Survey (NFHS-4) conducted in 2015-16. Our analysis has divided the uses of contraception into three modern methods of family planning such as Short-Acting Reversible Contraception (SARC), Long-Acting Reversible Contraception (LARC) and permanent contraception methods. SARC includes pills, injectable, and condoms, while LARC includes intrauterine devices, implants, and permanent contraception methods (i.e., male and female sterilization). We have employed a concentration index to examine the level of socioeconomic inequalities in utilizing modern contraception methods. Results Our results show that utilization of permanent methods of contraception is more among the currently married women in the higher age group (40-49) as compared to the lower age group (25-29). Women aged 25-29 years are 3.41 times (OR: 3.41; 95% CI: 3.30-3.54) more likely to use SARC methods in India. Similarly, women with 15 + years of education and rich are more likely to use the LARC methods. At the regional level, we have found that southern region states are three times more likely to use permanent methods of contraception. Our decomposition results show that women age group (40-49), women having 2-3 children and richer wealth quintiles are more contributed for the inequality in modern contraceptive use among women. Conclusions The use of SARC and LARC methods by women who are marginalized and of lower socioeconomic status is remarkably low. Universal free access to family planning methods among marginalized women and awareness campaigns in the rural areas could be a potential policy prescription to reduce the inequalities of contraceptive use among currently married women in India.